Representações sociais sobre a sexualidade : um estudo com discentes surdos - Guimarães, Valéria Maria Azevedo (2019)
Sexuality is present in the development of the human, it is being manifested in different ways according to each phase of the subject. Despite being a thematic published in the media, it is still notorious the existence of myths and taboos in the current society, which compromises in the transmission of information on this subject. In this sense, this study aims to understand the social representations of deaf sexuality and seeks to understand the social representations that deaf students have about sexuality, and their actions are influenced by these representations. This research had as theoretical contribution the Theory of Social Representations, which allows to elucidate the historical, cultural and political aspects that surround the subject and with this access the knowledge coming from the common sense, with the scientific understanding about sexuality. For that, the dissertation was structured in 3 chapters presented in the article format (2 systematic reviews and 1 empirical study). In Chapter 1, a systematic review on social representations and deafness was developed in five databases (SciELO, PePSIC, LILACS, PsycINFO and Scopus) from 1990 to 2017. Chapter 2 addressed sexuality and deafness through the systematic review, from 2000 to 2017, using SciELO, PePSIC, LILACS, PsycINFO and Scopus as databases. Chapter 3 had a sample of 10 deaf students from elementary school (9th grade) and middle school (1st, 2nd and 3rd year). The social representations of the sexuality of these participants were anchored in the care with sexual health, in the relations with the pairs, with the family and in the intimate relations of affection. Analyzes of the empirical studies were elaborated by IRAMUTEQ software. According to the chapters produced, the scarcity of studies on social representations, deafness and sexuality was noticed, and that the subject of sexuality is little debated in the family environment. In this way, the friends, the boyfriend and the teachers were the most cited as sources of information. It is worth emphasizing that the focus of the guidelines received by the students was aimed at the prevention of risk behaviors of the deaf youth.